Using student views to develop a formative assessment policy in a sixth-form History department - Hawkins, E (2016)
This project sought to explore the views of sixth-form history students concerning the efficacy of their department’s formative assessment policy, and builds on my part 2 research into student views of self and peer marking. The project first consisted of a literature review in order to provide the grounding needed to adapt the department’s current assessment policy. This policy was then implemented by all staff in the department at the start of the academic year. Questionnaires and group interviews were carried out to explore how the students responded to this policy, with the intention that their responses would then be mediated by staff to produce an adapted policy for the start of the next academic year. One of the key findings of this project was that despite increased student confidence in self assessment, students still reported considerable reliance on the teacher. Among other conclusions drawn, it will ultimately be suggested that to further shift the balance of power in assessment away from the teacher, students need greater ownership not only over the assessment of their work, but also the assessment policy itself. Therefore, although the original aim of the project was for the staff to redraft the department’s assessment policy based on student views, instead the outcome developed into a decision to give students a role in regularly revising the policy, encouraging a more organic and embedded approach. Although this approach to policy-making in general is far from novel, it is rarely applied specifically to formative assessment, where educationalists tend to empower students within the narrow boundaries of teacher-determined assessment activities. It is still often the teacher ultimately who ‘owns’ and ‘provides’ formative assessment activities, with students required only to play their ascribed role. Therefore, this approach contrasts considerably with some of the contemporary literature that sees formative assessment as a concern of teacher pedagogy rather than student ownership.